Stability of metal–organic frameworks under gamma irradiation. Issue 84 (5th October 2016) - Volkringer, C.; Falaise, C.; Devaux, P.; Giovine, R.; Stevenson, V.; Pourpoint, F.; Lafon, O.; Osmond, M.; Jeanjacques, C.; Marcillaud, B.; Sabroux, J. C.; Loiseau, T.
Abstract : We report the study of the resistance of archetypal MOFs (MILs, HKUST-1, UiO-66, and ZIF-8) under gamma irradiation. Abstract : We report the study of the resistance of archetypal MOFs (MILs, HKUST-1, UiO-66, and ZIF-8) under gamma irradiation. The different porous solids were irradiated with doses up to 1.75 MGy. All the MOFs constructed with transition metals (Cu 2+, Zn 2+, Zr 4+ ) exhibit an evident destruction of the framework, whereas the compounds constructed with aluminium remain intact.